Making of Biodegradable Plastic Based on Corn Starch (Amylum Maydis) with Addition of Acid (CH3 COOh) and Gliserol Plasticizer - Desti Yuspita Sari; - Ratnawulan; Riri Jonuarti; Rahmat Hidayat (Department of Physics – Universitas Negeri Padang UNP, 2023)
Almost all countries face the problem of plastic waste due to the large production of conventional plastics and the long degradation process. Therefore, to protect nature from the accumulation of plastic waste, research on biodegradable plastics needs to be done. Biodegradable plastics are made from starch, cellulose, chitosan, and proteins extracted from renewable biomass. Starch for making biodegradable plastics can be obtained from plants, one of which is corn. This study aims to determine the effect of the composition of acetic acid, glycerol and corn starch on the quality of biodegradable plastics which include tensile strength, elongation and biodegradation. The independent variables were variations of acetic acid and glycerol. Control variables are plastic mold size, corn starch mass of 5 grams, other compounds outside the independent variables. The dependent variable is tensile strength, elongation and biodegradation. To test the tensile strength and elongation of biodegradable plastic, Ultimate Testing Machine Mini was used. The results showed that the addition of acetic acid and glycerol to the corn starch and glycerol blending material had an effect on increasing the tensile strength value and reducing the elongation and biodegradation values of biodegradable plastics. The highest tensile strength value is 50.04 Mpa, obtained from the addition of 1.44% acetic acid and 35.71% glycerol from a volume of distilled water of 70 ml. The highest length gain or elongation of 90% was obtained from the addition of 0.48% acetic acid and glycerol as much as 21.43% of the 70 ml volume of distilled water. Percent weight loss of the largest plastic obtained from the addition of acetic acid as much as 0.48% and glycerol as much as 21.43% of the volume of distilled water as much as 70 ml, which amounted to 93.33%.